Beowulf Cluster Computing with Linux, Second Edition - Gropp, William (The MIT Press, 2011)
This how-to guide provides step-by-step instructions for building a Beowulf-type computer, including the physical elements that make up a clustered PC, the software required, and insights on how to organize the code to exploit parallelism.